Thyroid disorders and gastrointestinal dysmotility: an old association - Xu, Guang-Meng; Hu, Ming-Xin; Li, Si-Yu; Ran, Xuan; Zhang, Hao; Ding, Xiang-Fu (Frontiers in Physiology, 2024)
Gastrointestinal motility symptoms may be closely related to thyroid diseases. Sometimes, such symptoms are the only thyroid disease-related clue although the degree of the symptoms may vary. The exact mechanism of action of thyroid hormones on gastrointestinal motility is not completely understood, however, a clue lies in the fact that muscle cell receptors can be directly acted upon by thyroxines. Both hypo- and hyperthyroidism can cause impairment of gastrointestinal motility, modifying structure and function of pharynx and esophagus, and regulating esophageal peristalsis through neuro-humoral interaction. In hyperthyroid patients, alterations of postprandial and basic electric rhythms have been observed at gastro-duodenal level, often resulting in slower gastric emptying. Gastric emptying may also be delayed in hypothyroidism, but an unrelated gastric mucosa-affecting chronic modification may also cause such pattern. Hyperthyroidism commonly show malabsorption and diarrhoea, while hypothyroidism frequently show constipation. In summary, it can be stated that symptoms of gastrointestinal motility dysfunction can be related to thyroid diseases, affecting any of the gastrointestinal segment. Clinically, the typical thyroid disease manifestations may be missing, borderline, or concealed because of intercurrent sicknesses. Motility-linked gastrointestinal problems may easily conceal a misdetected, underlying dysthyroidism that should be carefully analyzed. Here, we aim to elaborate on the associations between thyroid disorders and GI dysmotility and the common clinical manifestations associated with GI dysmotility.